The lost battalions : a battle that could not be won, an island that could not be defended, an ally that could not be trusted - Gilling, Tom (Allen & Unwin, 2018)
A little known story of two Australian battalions abandoned in Java during World War II and the heroes who kept them alive in the worst of Japan's prisoner of war camps.